Advanced ultrasound vibration potential imaging - Fria Hossein; Panagiota Angeli (Chemical Physics Impact)
Ultrasound Vibration Potential Imaging (UVPI) involves the detection of an electric signal resulting from ultrasound pulses passing through ionic fluids or colloidal systems. The process encompasses the exposure of ionic fluids, or nanoparticle suspensions to external ultrasound pressure waves, inducing ions and nanoparticles to vibrate and produce an electric potential. This potential is then recorded using an electrode sensor connected to the sample of interest. This article reviews the main concepts of UVPI, including the two main types of the technique, Colloid Vibration Potential (CVP) and Ion Vibration Potential (IVP). It is shown that UVPI can detect physicochemical structures of ions and tissue strata that are indiscernible through traditional ultrasound methods, examining specimens like ionic solutions, particle suspensions, and animal (pork) tissue. . The paper demonstrates the potential of UVPI in applications in engineering for nanoparticle and ionic electrolyte analysis, and in medical diagnostics and research. It can potentially be used for tumour diagnostics by analysing the vibrational responses of tissues to ultrasound waves, allowing for the early detection and characterization of tumours.